Efficiency in philanthropic organisations: a quantitative approach to performance assessment. (1st January 2013) - Milani Filho, Marco Antonio Figueiredo
In this study, I compare the production efficiency of the philanthropic organisations from São Paulo State, Brazil, dedicated to the elderly population. It was also investigated whether these entities' dependence level on public resources was significantly related with their efficiency level, calculated through data envelopment analysis. The sample included 42 asylum institutions, whose input data (capital and labour) were related with their products (performance indicators). The research hypothesis was tested through linear regression analysis. Differently from the initial expectations, the results indicated that no significant relation exists between dependence level on public resources and production efficiency level, suggesting that, in this case, the direct relation to government funding agencies it is not a factor to improve or to relax the organisational performance. I also pointed out benchmarks for inefficient entities, as a contribution to the respective performance improvement.